The Discovery of America? Representations of Columbus and Indigenous Peoples in Spanish Textbooks - Jerue, Benjamin A. (Clio. History and History Teaching, 2018)
This paper analyzes how five Spanish textbooks used in 2º ESO teach Columbus and his interaction with the indigenous peoples of America. Previous research has tended to focus on the diachronic evolution of textbook discourse or has compared the textbooks used in different countries. Furthermore, researchers have often assumed—or at least implied—that the “official” discourse found in a nation’s corpus of textbooks is more or less homogenous and hence can be boiled down to a set of standard traits. This paper, in contrast, highlights the meaningful differences between various Spanish textbooks’ treatment of the so-called “Discovery of America.” Despite this diversity of approach, none of books examined will satisfy recent calls for minimizing Eurocentric perspectives in teaching students about the Americas.
Keywords: Discovery of America; Columbus; indigenous peoples; Eurocentrism; textbook; 2º ESO